Międzykoręgowe zawody piłki nożnej o Puchar Dr J. Michałowicza. (Gdynia : [s.n.], 1970)
Afisz inf. o zawodach 28-31.05.1970 r.
Keywords: Piłka nożna -- Polska -- 1945-1970.; Gdańsk (Polska) -- 1945-1970 -- druki ulotne